Bienestar psicológico en mujeres sindicadas del establecimiento penitenciario y carcelario de mediana seguridad de Buenaventura - Góngora Hurtado, Delyn (Universidad Antonio Nariño, 2021)
The main objective of this study has been to establish psychological well-being, in greater and lesser presence in unionized women of the Buenaventura Medium-Prison and Prison Establishment. Six dimensions of psychological well-being have been taken into account for its development. This study is of a descriptive-non-experimental crosssectional type, the research was carried out with 12 syndicates, this being the universe of the population. In the investigation, the BP questionnaire by Ryff (1989) was used as an instrument, in its adaptation and validation Colombian by Pineda, Castro and Chaparro (2017). The results showed a high presence of psychological well-being in the dimension of personal growth and a greater deficit in the dimension of autonomy, favoring in the research process discussions that have enriched the field of psychological well-being and contributions for subsequent studies.